Characteristics and Mother Behavior about Pneumonia Prevention in Children - Lindesi Yanti; Rizanda Machmud; Lili Fajriah (Jurnal Ilmu Keperawatan Jiwa, 2020)
Providing education on the prevention of pneumonia is an effort to reduce morbidity and mortality among children under five. However, after education on mothers of children under five, the incidence of pneumonia is still high. This research is a descriptive study that aims to explore the characteristics and behavior of mothers regarding the prevention of pneumonia. This is done to be able to plan the provision of further interventions for mothers of children under five. The sampling technique used non-probability methods with total sampling techniques totaling 76 respondents. The research instrument used KAP(Knowledge, Attitudes, and Practices) with a total of 32 questions, Cronbach alpha knowledge (0.844), attitude (0.807), and action (0.826). Data analysis using analysis univariate. Characteristics of respondents aged 18-40 years (90.8%), most education was high school (65.7%), and non-working / housewives (85.5%). Mean knowledge value7.55,  attitude with the mean value 26.16, and measures with a mean value of 27.22. Based on the conclusions of the results of research on maternal behavior regarding the prevention of pneumonia in children under five associated with inadequate risk factors for pneumonia, it can cause toddlers to have a risk of pneumonia.